Effect of sintering temperature variations on fabrication of 45S5 bioactive glass-ceramics using rice husk as a source for silica - Leenakul W. (2017)
© 2015 Elsevier B.V. All rights reserved. 45S5 bioactive glass is a highly bioactive substance that has the ability to promote stem cell differentiation into osteoblasts - the cells that create bone matrix. The aim of this work is to analyze physical and mechanical properties of 45S5 bioactive glass fabricated by using rice husk ash as its silica source. The 45S5 bioactive glass was prepared by melting the batch at 1300 °C for 3 h. The samples were sintered at different temperatures ranging from 900 to 1050 °C with a fixed dwell-time of 2 h. The phase transitions, density, porosity and microhardness values were investigated and reported. DTA analysis was used to examine the crystallization temperatures of the glasses prepared. We found that the sintering temperature had a significant effect on the mechanical and physical properties of the bioactive glass. The XRD showed that when the sintering temperature was above 650 °C, crystallization occurred and bioactive glass-ceramics with Na 2 Ca 2 Si 3 O 9 , Na 2 Ca 4 (PO 4 ) 2 SiO 4 and Ca 3 Si 2 O 7 were formed. The optimum sintering temperature resulting in maximum mechanical values was around 1050 °C, with a high density of 2.27 g/cm 3 , 16.96% porosity and the vicker microhardness value of 364 HV. Additionally, in vitro assay was used to examine biological activities in stimulated body fluid (SBF). After incubation in SBF for 7 days, all of the samples showed formations of apatite layers indicating that the 45S5 bioactive glasses using rice husk as a raw material were also bioactive.